How Can Insurers Become Effective E-Carriers? An exploratory study in Malaysia - Samiappan, Mahendran (2007)
Internet retailing offer consumers with unparalleled opportunity and benefits to locate, to compare and customize the product need, has tremendously changed the way things are bought and sold in the markets. In insurance, firms are beginning to offer a wide array of online services, including online sales, needs analysis, and customer service. Together with other important trends such as globalization and regulatory reform, these developments are forcing far-reaching changes upon the insurance industry and making it more competitive. While insurance purchasers have more options available today, it is unclear if and when the Internet channel will dominate the traditional agent-led distribution channels. Therefore insurers face the challenge to understand the customer segment that is more prone to transacting via the internet, the type of products preferred by the consumer for online purchase and the quality dimensions they look forward to whilst making an online purchase. In this research, the afore mentioned elements have been examined in the Malaysian context. The results of the survey supports that consumers with prior experience of purchasing via the internet have higher propensity to purchase insurance online. It has also revealed that simple and straightforward products, such as travel, personal accident and auto insurance are preferred to be purchased over the internet as compared to life and health insurance. The study has also revealed that insurers should pay much attention to the infrastructure and web design of the portal to be used for online transactions. Download speed and ease of navigation are important factors to an online consumer. Therefore, insurers should have the right strategies in venturing into online retailing in order to maximize their investment.